Family therapy with ethnic minorities - Ho, Man Keung; Rasheed, Janice M. (Janice Matthews); Rasheed, Mikal N. (Mikal Nazir); Sage eBooks (Thousand Oaks ; London : SAGE, 2004)
Janice Matthews Rasheed (Loyola U., Chicago) and Mikal Rasheed (Northeastern Illinois U.) provide a revised edition of the 1987 text by the late Dr. Man Keung Ho, written for advanced students and practitioners working in clinical practice with American racial and ethnic minority families. The new edition updates the various demographics, and incor.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Family psychotherapy -- United States; Minorities -- Mental health services -- United States; Electronic books